EXPERIENCING CORE SYMPTOMS OF ANXIETY AND UNIPOLAR MOOD DISORDERS IN LATE ADOLESCENCE PREDICTS DISORDER ONSET IN EARLY ADULTHOOD. Issue 3 (27th February 2014) - Wolitzky‐Taylor, Kate; Dour, Halina; Zinbarg, Richard; Mineka, Susan; Vrshek‐Schallhorn, Suzanne; Epstein, Alyssa; Bobova, Lyuba; Griffith, James; Waters, Allison; Nazarian, Maria; Rose, Raphael; Craske, Michelle G.
<x xml:space="preserve">Abstract</x> Background Identification of youth at risk for anxiety and unipolar mood disorders (UMDs) can improve public health by targeting those who may warrant early or preventive intervention. This study examined whether endorsing core features of anxiety and UMDs predicted onset of later anxiety and UMDs across the next 7–9 years, and whether having subthreshold or subclinical manifestations of these disorders similarly predicted onset. Methods Data from this study come from the Youth Emotion Project (YEP), a two‐site investigation of common and specific risk factors for emotional disorders. Endorsement of core features of a disorder and subclinical or subthreshold anxiety and UMD diagnoses were determined using data from the Structured Clinical Interview for DSM‐IV (SCID) at the baseline assessment. Participants completed annual SCIDs over the course of the next 7–9 years (depending on cohort). Results Endorsement of panic attacks, obsessions and/or compulsions, and depression and/or anhedonia predicted onset of panic disorder, obsessive compulsive disorder, and major depressive disorder, respectively. When including all anxiety disorders in a model, only the presence of panic attacks uniquely predicted anxiety disorder onset. The presence of subclinical or subthreshold panic disorder, obsessive compulsive disorder, and social phobia at baseline predicted the full onset of these disorders over the follow‐up period. Conclusions Experiencing some symptoms of anxiety and UMDs in the absence of meeting diagnostic criteria is indicative of risk for later onsets of clinically significant DSM manifestations of these disorders. These individuals should be identified and targeted for prevention programs.